Nanomaterials in drug delivery, imaging, and tissue engineering - Tiwari, Ashutosh, 1978-; Tiwari, Atul. (Hoboken, New Jersey : John Wiley & Sons, 2013)
"Nanoscopic therapeutic systems incorporate therapeutic agents, molecular targeting and diagnostic imaging capabilities and are emerging as the next generation of multifarious nanomedicine to improve the therapeutic outcome including chemo and translational therapy. This reference work is one of the first to cover Nanotheragnostics which is the new edge of nanomedicine combining both diagnostic and therapeutic elements at nano level.This large multidisciplinary reference work is has four main parts: Biocompatible Nanomaterials; Nanomedicine: Drug Gene and Cell Delivery; Multi-functional Nanocarrier: Diagnosis, Imaging and Treatment; Tissue Engineering/Regenerative Medicine"--
"This book is written for a large readership including university students and researchers from diverse backgrounds such as chemistry, materials science, physics, pharmacy, medical science, and biomedical engineering"--
Includes bibliographical references and index.
Keywords: Biomedical materials; Drug delivery systems; Tissue engineering; SCIENCE / Biotechnology